Synaptic Failure Differentially Affects Pattern Formation in Heterogenous Networks - Budak, Maral; Zochowski, Michal (Frontiers in Neural Circuits, 2019)
The communication of the neurons is maintained by synapses, which play a crucial role in the functioning of the nervous system. Therefore, synaptic failure may impair information processing in the brain, to the extent of the loss of consciousness, as well as may underlie many neurodegenerative diseases. Moreover, a number of studies suggested that anesthetics regulate conscious state by affecting synaptic transmission primarily of network hubs and subsequently reducing the coherence in the network activity. Here, we studied network-wide spatio-temporal patterning in scale-free networks with two types of synaptic failure: activity-dependent and activity-independent. Further, we defined scale-free network structures based on the dominating direction of the connections at the hub neurons: incoming and outgoing. We found that the two structures have significantly different dynamical properties. Moreover, synaptic failure may not only lead to the loss of coherence but, under some conditions, also can facilitate its emergence unintuitively. We showed that this is because activity-dependent synaptic failure homogenizes the activity levels in the network creating a dynamical substrate for the observed coherence increase. Our results indicate that coherence breakdown due to the synaptic failure may not be enough to explain the loss of consciousness, but at the same time can lead to such pathologies as epilepsy.